Phagocytic and Bactericidal Properties of Channel Catfish Peritoneal Macrophages Exposed to Edwardsiella ictaluri Live Attenuated Vaccine and Wild-Type Strains - Kordon, Adef O.; Abdelhamed, Hossam; Ahmed, Hamada; Park, Joo Y.; Karsi, Attila; Pinchuk, Lesya M. (Frontiers in Microbiology, 2018)
ABSTRACT Edwardsiella ictaluri (E. ictaluri), a Gram-negative, intracellular, facultative bacterium, is the causative agent of enteric septicemia of catfish (ESC), which is one of the most significant diseases of farmed channel catfish. Macrophages have a critical role in major defense mechanisms against bacterial infections by migrating to the site of infection, engulfing and killing pathogens, and priming adaptive immune responses. Vaccination of catfish with E. ictaluri live, attenuated vaccine (LAV) strains increased the efficiency of phagocytosis and bacterial killing in catfish peritoneal macrophages compared in vitro with macrophages from non-vaccinated fish. Recently, our group developed several protective LAV strains from E. ictaluri. However, their effects on the antigen uptake and bacterial killing in catfish macrophages have not been evaluated. In this study, we assessed the phagocytic and bactericidal activity of peritoneal macrophages in the uptake of E. ictaluri wild-type (WT) and two LAV strains. We found that phagocytosis of LAV strains was significantly higher compared to their WT counterpart in peritoneal macrophages. Moreover, the uptake of E. ictaluri opsonized with sera from vaccinated catfish was more efficient than when opsonized with sera from sham vaccinated fish. Notably, catfish macrophages did not lose their phagocytic properties at 4o C, as described previously in mammalian and zebrafish models. Also, opsonization of E. ictaluri with inactivated (IN) sera from vaccinated and sham vaccinated catfish decreased significantly phagocytic uptake of bacteria at 32o C, and virtually suppressed endocytosis at 4o C, suggesting the important role of complement-dependent mechanisms in catfish macrophage phagocytosis. In conclusion, our data on enhanced phagocytic capacity and effective killing ability in macrophages of vaccine strains suggested the LAVs’ advantage if processed and presented in the form of peptides to specific lymphocytes of an adaptive immune system and emphasize the importance of macrophage-mediated immunity against ESC. Furthermore, we showed the role of complement- dependent mechanisms in the phagocytic uptakes of E. ictaluri in catfish peritoneal macrophages at 4oC and 32oC. Finally, LAV vaccine-induced bacterial phagocytosis and killing properties of peritoneal macrophages emphasized the importance of the innate immune responses in ESC.